Microwave dieletric properties of the abscission layer of oil palm - Sukaribin, Nazarulhisyam; Khalid, Kaida (2007)
The world production of palm oil for 2005 was about 33.33 million metric tones and is now one of the worlds most widely consumed edible oil.The process of getting the oil from the mesocarp, fruitlets muct be detached from the bunch. Through the natural process of fruits loosening, the fruit shedding take palce by the cell separation at the abscission zone and followed by further cell separation in peripheral tissue near the zone. Conventionally, in the oil mill, the sterilization process is used to activate the oil splitting enzyme and to loosen the fruits in the bunch. This sterilization process is done under high pressure at 3 bars and requires high-pressure steam to heat the oil palm bunches for almost 2 hours and is done in beatches. With the current microwave technology there is a possibility to introduce microwave sterilization which will be able to do the same job done by the conventional sterilizer including loosening of fruits from the bunch. In this paper, a study on the dielectric properties and moisture content surrounding the abscission layer of oil palm fruits is described. This work will give a better understanding of how microwave interacts with the abscission layer of the oil palm bunch, thus providing information for better engineering design of the microwave sterilization system.